PENGARUH VITAMIN C TERHADAP C-REACTIVE PROTEIN SEBAGAI PETANDA INFLAMASI PADA GAGAL GINJAL KRONIK DENGAN HEMODIALISIS REGULER - Wulandari, Diah Catur; Suwitra, Ketut (journal of internal medicine, 2008)
One of possible treatment to diminish the inflammation in regularly hemodialysis chronic kidney disease (RHCKD) isantioxidant. Ascorbic acid can inhibit nuclear factor B (NF-B) activation, decrease C-reactive protein (CRP) levels. The objectiveis to determine whether ascorbic acid 1000 mg intravenously can decrease CRP levels in RHCKD. In this randomized singleblind controlled clinical trial, thirty two patients were recruited. CRP was examined at baseline and 4 weeks. Permutted blockrandomization was done to receive vitamin C 1000 mg or NaCL 0.9%. CRP levels were compared between the two groups asprimary outcome. During study 16 patients were received i.v. ascorbic acid 1000 mg and 16 patients were received NaCl 0.9%.One of patient in vitamin C 1000 mg group was dropped out due to infection. During follow-up, both groups showed increased ofCRP among ascorbic acid 1000 mg groups (from 1.77 ± 1.41 mg/L before to 1.83 ± 1.78 mg/L after study; increase by 0.06 ± 1.38mg/L; 95% CI -0.20 ? 0.28 P = 0.72) and among NaCl 0.9% group (from 2.83 ± 2.86 mg/L before to 2.98 ± 3.29 mg/L afterstudy increase by 0.15 ± 1.38 mg/L 95% CI -0.14 ? 0.11 P = 0.82 ). Although CRP levels were increased, no statistically differentof CRP increament in both groups. The conclusion of this study is ascorbic acid 1000 mg during 4 weeks can not decrease CRPlevels in RHCKD.